2005
DOI: 10.1002/jmv.20426
|View full text |Cite
|
Sign up to set email alerts
|

Replication of TT virus in hepatocyte and leucocyte cell lines

Abstract: The TT virus (TTV) is a non-enveloped, single-stranded, circular, DNA virus, first isolated from a patient with hepatitis of unexplained etiology. The much deliberated pathological role of the virus continues to be conjectural in the absence of a suitable in vitro replication model. So far, the liver and the bone marrow have been shown to be the main sites of TTV replication. In this study, the human cell lines HepG2 and Chang Liver, the rat hepatoma cell line MH1C1, phytohemagglutinin (PHA)-stimulated TTV-neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…Peripheral blood mononuclear cells (PBMCs) were thought to act as a reservoir for TTV but double stranded intermediates have not been isolated from these cells suggesting that this is not a site of replication [Okamoto et al, 2000b]. However, TTV replication has been achieved in vitro by stimulation of PBMCs with phytohemagglutinin, lipopolysaccharide, and interleukin-2 [Mariscal et al, 2002;Desai et al, 2005]. Similar titers of TTV/TTMV in bone marrow and spleen suggests either the spleen is also a site of replication or the infiltration of spleen by cell types supporting replication.…”
Section: Discussionmentioning
confidence: 98%
“…Peripheral blood mononuclear cells (PBMCs) were thought to act as a reservoir for TTV but double stranded intermediates have not been isolated from these cells suggesting that this is not a site of replication [Okamoto et al, 2000b]. However, TTV replication has been achieved in vitro by stimulation of PBMCs with phytohemagglutinin, lipopolysaccharide, and interleukin-2 [Mariscal et al, 2002;Desai et al, 2005]. Similar titers of TTV/TTMV in bone marrow and spleen suggests either the spleen is also a site of replication or the infiltration of spleen by cell types supporting replication.…”
Section: Discussionmentioning
confidence: 98%
“…There are no reports of a culture system to support the replication of TTV effectively, except for the minimal growth in PBMC and Chang liver cells [48,53]. However, most of the TTV sequences reported in the database possessed a common arrangement of frameworks and continuous open reading frames.…”
Section: Diversity Of the Ttv Genomementioning
confidence: 92%
“…Moreover, the TTV þ signal disappeared in PBMCs after degradation of ssDNA by mung bean nuclease [51]. In the study by Desai et al [48], PBMCs stimulated with PHA and also Raji cells transiently supported virus replication. But as before, quantitative analysis of these observations is lacking.…”
Section: Target Cells Of Ttvmentioning
confidence: 96%
See 1 more Smart Citation
“…Certain endogenous and exogenous factors can act as cofactors by influencing the risk of HPV persistence and cancer progression. TTV replication has been demonstrated in hepatocyte and leukocyte cell lines (Desai et al 2005). Barril et al (2000) observed the presence of TTV in serum and peripheral mononuclear cells from continuous ambulatory peritoneal dialysis using primers for the ORF1 and ORF 2 regions of TTV.…”
Section: Resultsmentioning
confidence: 99%